Investigation of hydrogel membranes containing combination of gentamicin and dexamethasone for ocular delivery - Prabhu, Prabhakara; Dubey, Akhilesh; Parth, Vinod; Ghate, Vivek (International Journal of Pharmaceutical Investigation)
Background: Hydrogel is a cross-linked network of polymers. Water penetrates these network causing swelling and giving the hydrogel a soft and rubbery consistency and there by maintaining the integrity of the membrane. Due to the drawback of conventional therapy for ocular delivery, hydrogel membranes containing the combination of gentamicin (GT) sulfate and dexamethasone (DX) were formulated for the treatment of conjunctivitis. The objective of this study was to formulate and evaluate the hydrogel membranes containing the combination of GT and DX for the treatment of conjunctivitis. Materials and Methods: In the present investigation, hydrogel membranes were prepared by using polymers such as gelatin, polyvinyl alcohol, and chitosan, which were cross-linked using physical/chemical methods. Results: The cross-linking of the membranes was confirmed by Fourier transform infra-red studies. The pH of the membranes ranged from 7.19 to 7.45 and drug content ranged from 69.82% to 89.19%. The hydrogels showed a considerably good swelling ratio ranging from 22.5% to 365.56%. The in vitro drug release study showed that there was a slow and sustained release of the drug from the membranes which were sufficiently cross-linked and followed zero order release. In vivo studies showed that the severity of conjunctivitis was remarkably lowered at day 3 with hydrogel membrane compared to marketed eye drops. Results of unpaired t-test of significance between two groups indicated that the hydrogel membrane showed a better response in the treatment of conjunctivitis compared to the marketed products. Stability studies proved that the formulations could be stable when stored at room temperature. Conclusion: Results of the study indicated that it is possible to develop a safe and physiologically effective hydrogels which are patient compliant.
Keywords: Conjunctivitis; cross-linking; Fourier transform infra-red; hydrogels; polyvinyl alcohol